2013
DOI: 10.1186/1550-2783-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an isotonic beverage on autonomic regulation during and after exercise

Abstract: BackgroundWith prolonged physical activity, it is important to maintain adequate fluid balance. The impact of consuming isotonic drinks during and after exercise on the autonomic regulation of cardiac function is unclear. This study aimed to analyze the effects of consuming an isotonic drink on heart rate variability (HRV) during and after prolonged exercise.MethodsThirty-one young males (21.55 ± 1.89 yr) performed three different protocols (48 h interval between each stage): I) maximal exercise test to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 34 publications
1
64
1
5
Order By: Relevance
“…Only series with more than 95% sinus rhythm were included in the study. [13,14] To analyze HRV in the frequency domain, low frequency (LF: 0.04 to 0.15 Hz) and high frequency (HF: 0.15 to 0.40 Hz) spectral components were used in ms 2 and normalized units. Normalizing data of the spectral analysis can be used to minimize the effects of changes in the very low frequency (VLF) band.…”
Section: Linear Indices Of Heart Rate Variabilitymentioning
confidence: 99%
“…Only series with more than 95% sinus rhythm were included in the study. [13,14] To analyze HRV in the frequency domain, low frequency (LF: 0.04 to 0.15 Hz) and high frequency (HF: 0.15 to 0.40 Hz) spectral components were used in ms 2 and normalized units. Normalizing data of the spectral analysis can be used to minimize the effects of changes in the very low frequency (VLF) band.…”
Section: Linear Indices Of Heart Rate Variabilitymentioning
confidence: 99%
“…7,8 This technique has been widely used to understand the phenomena involved in the autonomic nervous system in normal and pathological conditions. 9 While recognizing the importance of the autonomic nervous system to the organism, studies that describe the effects of resistance training on autonomic modulation are scarce when it comes to resistance training in a healthy young adult population.…”
Section: B Introductionmentioning
confidence: 99%
“…On the other hand, it was suggested that during hemodialytic hypotension, autonomic changes are different, and are characterized by parasympathetic activation and sympathetic withdrawal and, as indicated by temporaryincreases in the power of HF component [6][7][8].The main objective of our study is to describe the behavior of HRV during hemodialysis. In order to clarify this mechanism we aimed to evaluate the acute effects of hemodialysis on cardiac autonomic regulation in patients with chronic renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis in the time domain was performed by means of SDNN (standard deviation of normalto-normal RR intervals), the percentage of adjacent RR intervals with a difference of duration greater than 50ms (pNN50) and RMSSD (root-mean square of differences between adjacent normal RR intervals in a time interval) [8,9].…”
Section: Linear Indices Of Hrvmentioning
confidence: 99%
See 1 more Smart Citation